EVALUATING EFFECTIVENESS OF SCHOOL GUIDANCE AND COUNSELLING PROGRAMME IN K.E.E.A. MUNICIPALITY OF GHANA - Adam-Yawson, Nana; Arkorful, Paul; Oppong-Masu, Asihene; Insaidoo, Sylvester (American Journal of Education and Practice, 2021)
Purpose: This study intended to consider the patronage and effectiveness of guidance and counselling programmes offered to Junior High Schools (J.H.S.) students in the Komenda-Edina-Eguafo-Abrem (KEEA) Municipality in the Central Region of Ghana. Methodology: The researchers used exploratory research design for the study. The researchers considered all the 105 Junior High Schools (J.H.S.) in the Municipality as the subject for the study. The researchers sampled 50 schools for data collection. They (researchers) administered questionnaire to the headmasters and teachers in-charge of guidance and counselling in the selected 50 Junior High Schools (JHSs) arriving at a total of 100 respondents. The instruments used for data collection were questionnaire. Data gathered were analysed in tables and converting them into percentages. Findings: The findings revealed that, guidance and counselling services were available in the schools with qualified and experienced officers to handle issues as and when they happen. They also offer prompt response to such issues. It further came out that there were not even a single school in the Municipality, which had a place as an office earmarked for guidance and counselling services. There were also some interference from other teachers, parents and headmasters in the affairs of counselling which hampered the effectiveness of the guidance and counselling services. Some teachers too felt reluctant to report identified problems to the notice of the counselling coordinators. Unique Contribution to Practice and Policy: The researchers suggested that misconceptions that some teachers, parents and other stakeholders have about guidance and counselling services should be expunged from their minds. Finally, recommendations from the researchers were that, to improve the guidance and counselling services for junior high school students in KEEA Municipality there should be regular workshops and orientation for teachers who ate mandated to offer guidance and counselling services to students. Teachers should be made to understand that counselling is geared towards cooperation, teamwork and meant for all students and develop well in confidential setting. The researchers suggested that guidance and counselling services should be infused into the schools' timetable like the assembly and worship.